2014
DOI: 10.7554/elife.02630
|View full text |Cite
|
Sign up to set email alerts
|

Genome rearrangements and pervasive meiotic drive cause hybrid infertility in fission yeast

Abstract: Hybrid sterility is one of the earliest postzygotic isolating mechanisms to evolve between two recently diverged species. Here we identify causes underlying hybrid infertility of two recently diverged fission yeast species Schizosaccharomyces pombe and S. kambucha, which mate to form viable hybrid diploids that efficiently complete meiosis, but generate few viable gametes. We find that chromosomal rearrangements and related recombination defects are major but not sole causes of hybrid infertility. At least thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
165
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(180 citation statements)
references
References 65 publications
(128 reference statements)
15
165
0
Order By: Relevance
“…Many fungi are known to have evolved inversions of parts of their chromosomes, which can block recombination between chromosomes during meiosis [42,43]. Such recombination blocks are most easily observed when the effects are severe, which is the case in meiotic drive elements as seen in S. pombe [44] or the spore killers in Neurospora intermedia [45]. In both cases, rearrangements cause linkage between elements that together are beneficial.…”
Section: Sexual Reproduction and Recombinationmentioning
confidence: 99%
“…Many fungi are known to have evolved inversions of parts of their chromosomes, which can block recombination between chromosomes during meiosis [42,43]. Such recombination blocks are most easily observed when the effects are severe, which is the case in meiotic drive elements as seen in S. pombe [44] or the spore killers in Neurospora intermedia [45]. In both cases, rearrangements cause linkage between elements that together are beneficial.…”
Section: Sexual Reproduction and Recombinationmentioning
confidence: 99%
“…In the case of Sp/Sk hybrids (and likely other pairings), the infertility is caused by both chromosomal rearrangements and multiple meiotic drivers (Zanders et al, 2014; Avelar et al, 2013). Indeed, we previously found that genes on each of the three Sk chromosomes are capable of enacting gamete (spore)-killing meiotic drive against their Sp homologs (Figure 1A) (Zanders et al, 2014). However, the genes responsible for the drive phenotypes were unknown.
10.7554/eLife.26033.003Figure 1.A complex meiotic drive landscape on Sk and Sp chromosome 3 is revealed by recombination mapping.( A ) A cross between Sk and Sp generates a heterozygote that has low fertility and preferentially transmits Sk alleles on all three chromosomes into viable gametes (Zanders et al, 2014).
…”
Section: Introductionmentioning
confidence: 99%
“…In Sp , this region contains wtf4 and the wtf3 pseudogene. The syntenic region in Sk contains only one wtf gene, wtf4 . DOI: http://dx.doi.org/10.7554/eLife.26033.00310.7554/eLife.26033.004Breakpoints between Sp and Sk -derived DNA sequences.The introgression strains used in diploids 1–8 were sequenced and genotyped for single-nucleotide polymorphisms (SNPs) that reliably distinguish Sk and Sp as in (Zanders et al, 2014). The SNPs flanking the recombination event (left and right boundaries) that generated each breakpoint between Sp and Sk DNA for each introgression strain are shown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When suppressed and no longer able to manifest their selfish action, such genetic elements are predicted to decay with mutation in a manner similar to inactive transposable elements. In instances where they have not fully decayed but are nonetheless successfully suppressed, their presence can be revealed by crosses between closely related species which may genetically separate the toxinantidote locus from its suppressor (Tao et al, 2001(Tao et al, , 2007aZanders et al, 2014). Fig.…”
Section: Meiotic Drive: Challenging Mendelmentioning
confidence: 99%